Single-cell measurements and modelling reveal substantial organic carbon acquisition by Prochlorococcus - Wu, Zhen; Aharonovich, Dikla; Roth-Rosenberg, Dalit; Weissberg, Osnat; Luzzatto-Knaan, Tal; Vogts, Angela; Zoccarato, Luca; Eigemann, Falk; Grossart, Hans-Peter; Voss, Maren; Follows, Michael J; Sher, Daniel (Springer Science and Business Media LLC, 2023)
Abstract Marine phytoplankton are responsible for about half of the photosynthesis on Earth. Many are mixotrophs, combining photosynthesis with heterotrophic assimilation of organic carbon, but the relative contribution of these two lifestyles is unclear. Here single-cell measurements reveal that Prochlorococcus at the base of the photic zone in the Eastern Mediterranean Sea obtain only ~20% of carbon required for growth by photosynthesis. This is supported by laboratory-calibrated calculations based on photo-physiology parameters and compared with in situ growth rates. Agent-based simulations show that mixotrophic cells could grow tens of metres deeper than obligate photo-autotrophs, deepening the nutricline by ~20 m. Time series from the North Atlantic and North Pacific indicate that, during thermal stratification, on average 8–10% of the Prochlorococcus cells live without enough light to sustain obligate photo-autotrophic populations. Together, these results suggest that mixotrophy underpins the ecological success of a large fraction of the global Prochlorococcus population and its collective genetic diversity.